Proficiency Level in Biology among Grade 9 Entrants in a Public Secondary School - Manzanares, Razel; Linaugo, Joji (Technium Social Sciences Journal, 2022)
In post-pandemic, schools are re-opening their doors to in-person classes to cater to students who were to distance learning modality for two years. To determine the learners’ proficiency level in Biology, it is imperative to assess the most essential learning competencies (MELCs) to ascertain what competencies were missed so that teachers can come up with appropriate interventions. A descriptive-comparative research design was used to assess the proficiency level in MELCs in Biology of Grade 9 Entrants at a large rural secondary school in Central Negros Occidental, Philippines, during the S.Y. 2022-2023 when they were taken as a whole and grouped according to sex and family monthly income. Using a researcher-made Biology Proficiency Questionnaire based on MELCs, the study was conducted to 137 respondents who were identified through stratified random sampling. In data analyses, Mean, Standard Deviation, Kolmogorov-Smirnov, and Mann-Whitney U Test were employed. The overall result of the proficiency level in MELCs in Biology was low, and when grouped according to sex and family monthly income, the result was also low. Correspondingly, there was no significant difference in Biology proficiency level when grouped according to sex and family monthly income. With this, Strategic Intervention Materials (SIMs) were deemed relevant and timely to aid students in understanding the least learned MELCs.